Disparity in Corruption Based on Pancasila Values in Judges' Decisions - Febriansyah, Artha; Novianti, Vera; Banjarani, Desia Rakhma (Proceedings Series on Social Sciences & Humanities, 2025)
In reality, many perpetrators of corruption are relatively given light sentences. Even recently, many cases have been acquitted by regional corruption courts. This fact has created disparities both horizontally and vertically. Based on this background, it is necessary to analyze the disparity in corruption crimes based on Pancasila values in the judge's decision. The problem that will be discussed in this research is how is the disparity of corruption crimes based on Pancasila values in the judge's decision? This research uses normative legal research. The research results show that the disparity of corruption crimes is based on Pancasila values, which are based on divinity, humanity, unity, deliberation, representation, and justice. As for the disparity in corruption, which is based on the value of justice, it is based on the 5th precept of Pancasila, namely "Social justice for all Indonesian people". The value of justice can be applied to the evidentiary process during the law enforcement process for corruption.